2023
DOI: 10.1021/acsami.3c04758
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Mechanism in Acceptor- or Donor-Doped ZrO2 Bulk and Thin Films

Abstract: The leakage current in capacitors in future electronics should be highly suppressed to achieve low power consumption, high reliability, and fast data processing. Although considerable efforts have been directed at reducing the leakage current, fundamental studies on the effects of doping on bulk and thin-film materials have rarely been conducted. Herein, we investigated the effects of doping with acceptor and donor elements on the conduction of bulk and thin-film ZrO 2 and elucidated the underlying charge cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…However, other experiments by Kim et al found ∼0.17 and −0.13 exponents at high and low oxygen partial pressures, respectively. 35 The only conditions in which the conductivity is quasi-independent of the oxygen partial pressure are below 10 −5 atm at some temperatures. This supports the hypothesis that the A 6 B 2 O 17 oxides in most of the conditions studied in this work are mixed ionic-electronic conductors.…”
Section: Resultsmentioning
confidence: 99%
“…However, other experiments by Kim et al found ∼0.17 and −0.13 exponents at high and low oxygen partial pressures, respectively. 35 The only conditions in which the conductivity is quasi-independent of the oxygen partial pressure are below 10 −5 atm at some temperatures. This supports the hypothesis that the A 6 B 2 O 17 oxides in most of the conditions studied in this work are mixed ionic-electronic conductors.…”
Section: Resultsmentioning
confidence: 99%